Enhancing Listening Skill Through Narrative Text in Video Games - Jimmi, Jimmi; Kusuma, Pradipta Hadi; Yastanti, Unpris (Universitas Negeri Semarang, 2024)
This research aims to discover the types of narrative text through listening to video games. The research focuses focusing enhancing students’ listening skills through narrative text appearing in video games and how listening can be enhanced by narrative text video games. This research uses a qualitative descriptive method. The researcher collected some data through the video games and then continued to classify them into narrative text analysis, especially linear structure, and branch structure. The researcher employed E. Kleinman Carstensdottir and M.S El-Nasr’s theory to analyze the texts and filter them into the linear structure and branch structure categories. The results show that linear structures have cutscenes, character interactions, and task completion. The video games that represent this analysis to enhance listening are taken from Alan Wake 2. The branch structures have multiple endings, dialogue trees, and quick-times events. The video games that represent this analysis to enhance listening are taken from Detroit: Become Human. This analysis shows that narrative video games provide an effective and leisurely way for individuals to practice and enhance their listening skill.